The Roman cult of Mithras a cognitive perspective = Římský kult boha Mithry : pohled kognitivních věd - Martin, Luther H. 1937- (2006)
Explorations by cognitive scientists into the panhuman biases of and constraints upon the processing and transmission of perceptual as well as conceptual information by human brains promises historians a scientifically-based set of theories with which to reconstruct past scenarios with greater confidence than previous methods have allowed. This article exemplifies this promise by employing one cognitively based theory, based upon two distinct systems of human memory, for a preliminary study of the Roman Cult of Mithras. Historians have previously understood Mithraism as a cultic tradition with a more or less common cultic myth which historians - despite any textual evidence for the cult - might decode from its abundant material remains. The transmission of such a widely shared myth would have depended upon an encoding of such information into the semantic memory of initiates. The encoding of shared information into semantic memory requires, however, repetition and members of Mithraic groups were initiated but once into their respective initiatory grades. The emotional arousal associated with these rites suggests an encoding of the initiatory experience into episodic memory, recall from which results in solidarity - and even shared knowledge - among a particular group of initiates but argues against any Mithriac myth held in common by all Mithraic groups.
Výzkumy kognitivních vědců ohledně všelidských tendencí a omezení, které ovlivňují zpracování a přenos symslových a také pojmových informací lidským mozkem, slibují poskytnout historikům vědecky ukotvené teorie, s jejichž pomocí bude možné rekonstruovat minulé děje s větší mírou důvěryhodnosti, než jakou dovolovaly předchozí metody. Tento článek je názornou demonstrací těchto možností, neboť využívá jedné z kognitivních teorií, založené na dvou distinktivních typech lidské paměti, k předběžnému studiu římského kultu boha Mithry. Badatelé dříve chápali mithraismus jako tradici s více či méně široce sdíleným kultovním mýtem, který by jimi mohl být - navzdory neexistenci jakýchkoli literárních zdrojů - rozluštěn na základě bohatých pozůstatků hmotné kultury. Přenos široce sdíleného mýtu tohoto druhu by ale závisel na "zápisu" těchto informací do sémantické paměti zasvěcence. "Zápis" sdílených informací do sémantické paměti nicméně vyžaduje opakování. Členové mithristických komunit však podstoupili zasvěcení do svých příslušných iniciačních stupňů pouze jednou. Emoční vzrušení spojené s těmito rituály poukazuje spíše na "zápis" iniciační zkušenosti do paměti epizodické. Vzpomínky na události v ní uložené vedou k solidaritě - a dokonce sdílené znalosti - uvnitř konkrétní skupiny zasvěcenců, hovoří však proti představě mithraistického mýtu sdíleného v rámci všech mithraistických komunit.